A Method of Using Continuous Surface Magnetization and Friction Coefficient Variations for Monitoring the Tribological Properties of CrO2/SS400 Steel for the Flexible Gas Seal. Issue 3 (2nd July 2016) - Chang, Yuh-Ping; Chou, Huann-Ming; Lin, Meng-Jie; Huang, Zi-Wei
Abstract: The experimental results demonstrate that the dynamic variations in surface magnetization and friction coefficient showed great potential for determining the onset of CrO2 film fracture. It is also shown that the CrO2 film resulted in low friction and low surface magnetization during the friction process, and is wear-resistant. Therefore, this study is novel and practical for the industry. Graphical Abstract: CrO2 /SS400 sample demonstrates no rutting wear, high wear resistance, low friction coefficient, and low magnetization.